'Animals kill, that's how the world works' : the role of neutralisation and affirmation techniques in the discourse of animal product consumption - Tawast, Tea; Åhlvik, Therese (SLU/Dept. of Urban and Rural Development, 2017)
Despite the fact that the consumption of animal products gives rise to a number of negative environmental externalities, global consumption keeps increasing. Previous research has applied neutralisation and affirmation theory in order to understand (dis)engagement in pro-environmental behaviour, typically with a focus on the individual user of such discursive justification strategies. However, the present thesis recognises a need to address the interpersonal role of these techniques and their implications for how individuals communicate regarding environmental issues. The purpose of this study was to connect the cognitive processes of neutralisations and affirmations to the discursive practices of social interaction in the context of animal product consumption and pro-environmental behaviour. The aim was to explore the ways in which, and with what implications, these techniques are used by omnivores and vegans in social interaction. Qualitative data was gathered through four focus group sessions conducted with eighteen omnivorous and vegan pro-environmental students in the Swedish city of Uppsala. A dialogical discourse analysis of this data uncovered six topoi that proved useful when professing claims of (dis)engagement in consumption of animal products. Furthermore, this study discusses the emergent micro-deliberations, the extensive reference to non-present others, the dialectics between neutralisations and affirmations, the structuration dialectic of topoi and the implications for the discourse of animal product consumption. This study offer insights into the complexity of pro-environmental behaviour in the area of animal product consumption, insights that are of value for practical and policy interventions aimed at reducing such consumption by organisations and governments.